Major dietary patterns in relation to disease severity, symptoms, and inflammatory markers in patients recovered from COVID-19 - Ebrahimzadeh, Armin; Taghizadeh, Mohsen; Milajerdi, Alireza (Frontiers in Nutrition, 2022)
Background: Few studies have been done about dietary intakes in patients with COVID-19. Current retro-prospective study was done to investigate association between major dietary patterns and COVID-19 symptom, severity and inflammatory markers in recovered cases. Methods: Overall, 250 recovered cases completed study questionnaires providing data on demographic characteristics, dietary information, and COVID-19 outcomes in Shahid Beheshti hospital, Kashan. We used multivariable logistic regression models to assess association between major dietary patterns and study outcomes. All statistical analyses were done by SPSS version 16. Results: We identified three major dietary patterns including unhealthy, traditional and healthy dietary patterns. Serum levels of CRP and ESR were significantly higher in patients with unhealthy and traditional dietary patterns and lower in those with healthy dietary pattern. There was a significant direct relationship between unhealthy and traditional pattern with risk of severe COVID-19 and hospitalization duration and a significant direct association between unhealthy pattern and odds of convalescence duration. A significant inverse relationship was found between healthy pattern and risk of severe COVID-19 and odds of convalescence duration. We found a significant direct association between unhealthy pattern and odds of cough, fever, chilling, weakness, myalgia, nausea and vomiting and sore throat and between traditional pattern and odds of cough, fever, and chilling. In contrast, a significant inverse association was seen between healthy pattern and odds of dyspnea, weakness and sore throat. Conclusions: In conclusion, current study showed that high adherence to healthy pattern was associated with lower CRP and ESR levels and lower risk of severe COVID-19, hospitalization and convalescence duration in patients recovered from COVID-19. More adherence to unhealthy or traditional dietary patterns was associated with higher CRP and ESR levels and higher risk of severe COVID-19 and hospitalization duration. A direct association was found between unhealthy and traditional patterns and risk of some COVID-19 symptoms, while the association was inverse for healthy dietary pattern.